Nutritional evaluation of corn and sorghum crop residues - Taylor, R.K.; Kilgore, Gary L.; Higgins, James J.; Blasi, Dale A.; Duncan, Stewart R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crop residue samples from 22 grazed and nongrazed corn and sorghum residue fields across Kansas were collected every 2 weeks during the 1997/98 winter feeding season to evaluate quality and yield. Corn residue averaged about 2 ½ tons of total dry matter (DM)/acre, with the leaf fraction (attached and unattached) constituting about 60% of that residue. Unattached leaves represented 85% of the total leaf DM. Yield estimates for sorghum residue averaged over 2 tons/ acre. The stem component represented 55 to 60% of the total DM collected, and about 58% of the leaves remained attached to the stem.
Keywords: Beef; Crop residues; Forage quality